Interlayer destabilization process of natural and commercial bentonite incorporated Ethylene Vinyl Acetate (EVA) nanocomposite with hybrid silicate nanofillers / Asfa Amalina binti Ahmad Fauzi - Asfa Amalia Ahmad Fauzi (School of Materials Engineering, Universiti Malaysia Perlis, 2018)
In this research, the main objectives of study were to apply a new method called 'destabilization process' to exfoliate nanoclay (bentonite) and investigate its effectiveness in optimizing the mechanical and thermal properties of the EVA/hybrid-filler nanocomposite. The three specific objectives were ; to characterize and compare the morphology and exfoliation behavior of bentonite clay nanofiller upon the application of a new destabilizing technique with varying pH condition, salt concentration and ultra-sonication time ; to evaluate the mechanical properties, structure and morphology of the EVA nanocomposites incorporating the pristine and destabilized natural and commercial bentonites, in single and hybrid form ; to evaluate the thermal properties of the EVA nanocomposites incorporating the destabilized natural and commercial bentonites, in single and hybrid form.